1993
DOI: 10.1111/j.1600-0765.1993.tb01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Lethal photosensitization of bacteria in subgingival plaque from patients with chronic periodontitis

Abstract: Subgingival plaque samples from patients with chronic periodontitis were exposed to light from a 7.3 mW Helium/Neon laser for 30 s in the presence and absence of 50 micrograms/ml toluidine blue O as a photosensitizer. Viable counts of various groups and species of bacteria were carried out before and after irradiation. The median numbers of viable bacteria initially present in the 30-microliters aliquots irradiated were 1.13 x 10(5) cfu (aerobes), 4.08 x 10(5) cfu (anaerobes), 4.92 x 10(3) cfu (black-pigmented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
84
1
6

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 12 publications
0
84
1
6
Order By: Relevance
“…5,8,13,16,17,22 However, similar studies demonstrated that the reduction of S. mutans in carious dentin was less than that seen in suspension, and was also less than that attained in a collagen matrix. In that study, it was concluded that the time of contact between the bacteria and TBO was a critical factor.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…5,8,13,16,17,22 However, similar studies demonstrated that the reduction of S. mutans in carious dentin was less than that seen in suspension, and was also less than that attained in a collagen matrix. In that study, it was concluded that the time of contact between the bacteria and TBO was a critical factor.…”
Section: Resultsmentioning
confidence: 93%
“…[14][15][16][17][18] However, the use of LED-based light sources to activate photosensitizers for use against oral microorganisms is a recent development. Study of their use is important to promote the clinical use of LEDs instead of lasers for therapeutic applications in dentistry.…”
mentioning
confidence: 99%
“…The susceptibilities of both gram-positive and gram-negative oral bacteria to cyanine photosensitizers have been demonstrated (24). Cyanine photosensitizers have also been observed to have activity against oral streptococci present in plaque samples (15,26) and in a biofilm (25).…”
mentioning
confidence: 99%
“…23 Earlier studies illustrate that antimicrobial PDT has been effective in reducing the prevalence of pathogens on implant surfaces without any side effects on implants or surrounding bone and tissues. 24,25 However, there are very limited clinical studies and clinical effects of PDT have not yet been demonstrated. To the best of our knowledge, until now no investigation from randomized controlled clinical studies are available that determine the clinical effects of PDT in the treatment of peri-implant diseases.…”
Section: Introductionmentioning
confidence: 99%